2009
DOI: 10.5771/0935-9915-2009-1-34
|View full text |Cite
|
Sign up to set email alerts
|

The Manager and the Flexworker: An Interpretive Interactionist Perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…While this may not necessarily result in a worker being more satisfied with his/her current job, it may cause the employee to respond to the organization's greater trust with greater organizational commitment. For example, a qualitative study conducted by Richardson () found that employees who worked from home felt trusted by managers and were willing to engage in organizational citizenship behaviors as a way of “paying back” trust. We encourage future research to further explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…While this may not necessarily result in a worker being more satisfied with his/her current job, it may cause the employee to respond to the organization's greater trust with greater organizational commitment. For example, a qualitative study conducted by Richardson () found that employees who worked from home felt trusted by managers and were willing to engage in organizational citizenship behaviors as a way of “paying back” trust. We encourage future research to further explore this possibility.…”
Section: Discussionmentioning
confidence: 99%